Portfolio Diversification Benefits of Malaysia’s Stock Indices with Commodities: An Analysis Based on the MGARCH-DCC and Wavelet Techniques - Ahmad Monir Abdullah; Mohd Fahmi Ghazali; Hazriah Hasan; Rafiatul Adlin Mohd Ruslan; Wan Muhd Nasrul Hadi Wan Abdul Aziz; Hishamuddin Abdul Wahab (Penerbit UKM, 2024)
Indexed by Scopus/MyCite